Thermal performance deterrence caused by PCM inclusion in firefighting garments: The other side of the story. - André Fonseca (2021)
Firefighters usually encounter high heat flux exposures, which can cause severe burns. The addition of a phase change material (PCM) layer into a firefighting garment assembly has proven to be beneficial as it lowers the garments temperature during the fire exposure. However, after the fire exposure, accumulated heat in the PCM garment is discharged towards skin and environment which can have a negative influence on thermal performance. In this study, a one dimensional numerical approach was used to study the effect of environment parameters (ambient convective heat flux) as well as PCM parameters (latent heat, melting temperature) on the thermal performance of the firefighting garment, after the fire exposure. It was concluded that the amount and phase change temperature at which latent heat is discharged had a significant effect on thermal performance, depending on the heat exposure scenario. For high - intensity exposures, skin damage is promoted by an increase in both properties whilst for low intensity exposures, a decrease in melting temperature would promote greater skin damage. The results outlined in this paper could aid in the manufacture of PCM firefighting garments, as skin damage due to PCM resolidification might be an important parameter to take into account when maximizing thermal performance.